Pandemic Crisis in Online Media: Quantitative Framing Analysis on detik.com’s Coverage of Covid-19 - Justito Adiprasetio; Annissa Winda Larasati (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
This study shows how detik.com, a pioneer and one of the largest online media companies in Indonesia frames the Covid-19 pandemic crisis. From the 6713 news reports in January, February and March, the most dominant framing of the crisis that appeared in the coverage was attribution of responsibility, followed by frame of human interest, frame of morality, frame of conflict and the last is frame of economic consequences. The quantitative approach was used in this research to ensure that systematic analysis and non-arbitrary procedures can be carried out on large amounts of data. This study offered a better understanding on of how online media framed the crisis during the pandemic. The results of this study indicate that the frame of attribution of responsibility is not only the most widely used by detik.com, but also the most dominant when the government is the main source of the news. The form of attribution of responsibility in times of crisis tends to be stronger in the realm of government because crisis events are widespread, forming an experience felt at the national level. As a result, crisis events have the potential to become political symbols used in framing various debates regarding a policy in the long run. The average tone of news towards the government from January to March was positive, although it gradually became more negative.